HUBUNGAN PENGETAHUAN CARA MEMELIHARA KESEHATAN GIGI DAN MULUT DENGAN KARIES GIGI PADA SISWA KELAS I SMP MUHAMMADIYAH PONE KECAMATAN LIMBOTO BARAT KABUPATEN GORONTALO - Samuel Tambuwun; I Ketut Harapan; Susanti Amuntu (POLTEKKES KEMENKES MANADO, 2014)
Dental caries is limited to tissue damage teeth. Maintaining oral health is essential, some oral and dental problems occur because of our lack of knowledge and maintain oral health and therefore very necessary awareness to preserve and maintain healthy teeth to prevent dental caries. This study aimed to determine the relationship of knowledge how to maintain healthy teeth and mouth with dental caries in the first grade students of SMP Muhammadiyah Pone Limboto Western District of Gorontalo district. This study uses an analytical survey method with cross sectional study, conducted in April 2014, located in SMP Muhammadiyah Pone Limboto Western District of Gorontalo district. The sampling method is the total population of 56 students. Data were tabulated and analyzed using Chi-square test. The results of this study showed respondents have knowledge and good dental caries category consists of 24 students, knowledge is not good either category kariesnya of 20 students while the knowledge category is not good, not good caries total of 11 students and has a good knowledge of the category of no good caries 1 students. Chi-square statistical test showed no relationship between pengetahuaan way to maintain healthy teeth and mouth with dental caries in which the p-value 0.004 <α 0.05. The conclusion that the knowledge is very important because the better pengetehuan someone then would be good dental health status